Interaction of high-molecular-weight adiponectin concentration in blood serum with the risk of metabolic syndrome in women - O. D. Belyaeva; D. L. Brovin; O. A. Berkovich; T. L. Karonova; N. A. Korelskaya (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. The development of metabolic syndrome (MS) in patients with abdominal obesity (AO) may be associated with a low level of the adiponectin (AN) - protective adipocytokine. AN circulates in the blood in various molecular forms.The high molecular weight AN is assumed to have greater metabolic activity. It is currently not clear what level of high molecular weight adiponectin (HMWA) in women with AO is associated with MS and its components.The objective was to study the role of high molecular weight adiponectin in the development of metabolic syndrome in women with abdominal obesity.Methods and materials. 302 women with AO and 161 women without AO were examined. MS was diagnosed in 62.3 % of patients.Results. The concentration of total adiponectin (TAN) and HMAN in the blood serum in women with MS was lower than in patients without MS (p<0.05). According to logistic regression analysis, the most significant factors influencing the risk of MS were low concentration of HMAN in the blood, age, and body mass index (p <0.05).Conclusions. It was found that women with AO and HMAN concentration of less than 1.96 μg/ml in the blood had an increased risk of metabolic syndrome.